2019
DOI: 10.3390/ani9040191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of In Utero Heat Stress on Piglet Physiology and Behavior Following Weaning and Transport

Abstract: The study objective was to determine whether in utero heat stress (IUHS) affects piglet physiology and behavior following common production practices. A total of 12 gilts were confirmed pregnant and allocated to either heat stress (HS; n = 6) or thermoneutral (TN; n = 6) conditions on day 30–60 of gestation. At weaning (22.5 ± 2.3 days of age), 1 boar and 1 barrow of median weight were selected from each litter and transported for approximately 7 h. Piglets were then blocked into pens (n = 2/pen) by in utero t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Numerous factors are known to contribute to the color of fresh meat products including chronic and acute stress pre-slaughter, glycolytic potential, genetics, among others [ 46 ]. As previously mentioned, IUHS has been associated with energy metabolism [ 4 , 9 , 10 ] and the stress response [ 9 , 11 , 12 ] in swine. However, it appeared such differences did not have any meaningful effect on oxidative stability shown by instrumental display color and TBARS values, nor on the extent of protein denaturation shown by transmission values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous factors are known to contribute to the color of fresh meat products including chronic and acute stress pre-slaughter, glycolytic potential, genetics, among others [ 46 ]. As previously mentioned, IUHS has been associated with energy metabolism [ 4 , 9 , 10 ] and the stress response [ 9 , 11 , 12 ] in swine. However, it appeared such differences did not have any meaningful effect on oxidative stability shown by instrumental display color and TBARS values, nor on the extent of protein denaturation shown by transmission values.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in performance and carcass composition through IUHS are often attributed to differential energy metabolism, as several studies have observed changes in blood insulin levels and glucose metabolism [ 4 , 9 , 10 ]. Similarly, offspring exposed to IUHS often exhibit increased blood cortisol [ 11 , 12 ], although decreased blood cortisol was observed by Byrd et al [ 9 ] and Maskal et al [ 10 ] following prolonged stress exposure. The level of blood cortisol has been shown to be related to multiple carcass quality attributes such as a positive correlation to carcass weight and backfat thickness and a negative correlation to lean carcass content [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, during exposure to acute stressors (e.g., birth, social stress, handling stress, weaning), an increase in circulating and salivary cortisol 3 – 5 and adrenocorticotropic hormone (ACTH) 6 have been reported for IUHS pigs when compared to in utero thermoneutral (IUTN) pigs. Interestingly, the opposite is true following more prolonged stressors (e.g., transport), whereby circulating cortisol levels are reduced in IUHS compared to IUTN pigs 7 , 8 . In addition to hormonal influences, IUHS increases the incidence of stress-associated behaviors when pigs are exposed to common postnatal production stressors (e.g., weaning and/or transport) 5 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the opposite is true following more prolonged stressors (e.g., transport), whereby circulating cortisol levels are reduced in IUHS compared to IUTN pigs 7 , 8 . In addition to hormonal influences, IUHS increases the incidence of stress-associated behaviors when pigs are exposed to common postnatal production stressors (e.g., weaning and/or transport) 5 , 7 . However, although the aforementioned studies 3 8 have been instrumental in identifying how IUHS can impact postnatal measures of swine stress and welfare, none to our knowledge have attempted to elucidate mechanisms that underlie these responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation